Penerapan Metode Heart Metrics dalam Menganalisis User Experience Aplikasi E-Learning - Brahmantio Widyo Trenggono; Asif Faroqi; Anita Wulansari (STMIK Banjarbaru, 2022)
Analysis of student experience in using an e-learning product which is one of the learning support facilities, needs to be done as a reference to improve the quality of the e-learning product, in order to provide a good quality learning space. This study aims to find out what are the priorities for improvement in the e-learning application of the ILMU “Universitas Pembangunan Nasional Veteran Jawa Timur” based on the Heart Metrics measurement tool. Data was collected using a proportionate stratified simple random sampling approach. After the data is collected, the validity and reliability of the statement items are tested using Importance Performance Analysis (IPA). The results of the analysis show that there is a difference (gap) that is negative between perceptions and expectations, where the value of perception is smaller than expectations. Based on the results of the analysis, the largest gap value is in the Task Success variable with a 92.30% suitability level, which means that ILMU e-learning has not reached user expectations. The management of the ILMU e-learning manager is expected to pay more attention to the Task Success variable in order to improve the user experience on the e-learning.Keywords: Importance Performance Analysis; Gap; Perception; Expectations Abstrak. Analisis pengalaman mahasiswa dalam menggunakan sebuah produk e-learning yang menjadi salah satu fasilitas pendukung pembelajaran, perlu dilakukan sebagai acuan untuk meningkatkan kualitas produk e-learning tersebut, agar dapat menyediakan ruang pembelajaran yang berkualitas baik. Penelitian ini bertujuan untuk mengetahui hal apa yang menjadi prioritas untuk ditingkatkan pada aplikasi e-learning ILMU Universitas Pembangunan Nasional “Veteran” Jawa Timur berdasarkan alat ukur Heart Metrics. Pengumpulan data dilakukan menggunakan pendekatan proportionate stratified simple random sampling. Setelah data dikumpulkan, dilakukan uji validitas dan reliabilitas terhadap item pernyataan dengan menggunakan Importance performance analysis (IPA). Hasil analisis menunjukkan adanya perbedaan (gap) yang bernilai negatif antara persepsi dan harapan, dimana nilai persepsi lebih kecil dibandingkan harapan. Berdasarkan hasil analisis, nilai gap terbesar berada pada variabel Task Success dengan tingkat kesesuaian 92,30%, yang berarti e-learning ILMU belum mencapai harapan pengguna. Pihak manajemen pengelola e-learning ILMU diharapkan memberikan perhatian lebih pada variabel Task Success guna meningkatkan pengalama pengguna pada e-learning tersebut.Kata kunci: Importance Performance Analysis; Gap; Persepsi; Harapan